Continuous Architecture in Practice Software Architecture in the Age of Agility and DevOps - Erder, Murat; Pureur, Pierre; Woods, Eoin (Addison-Wesley Professional, 2021)
Revamp Your Architectural Practices for New Challenges, Environments, and Stakeholder Expectations "This book recognizes that software architecture is not the merely conceptual domain of disconnected experts but is the . . . give-and-take daily tussle of team members who have to balance trade-offs and competing forces to deliver resilient, high-performing, secure applications. . . . [It] bridges the significant gap between the 'Earth from orbit' view and the pavement-level view of refactoring microservice code." --Kurt Bittner, VP, Enterprise Solutions, Scrum.org Authors Murat Erder, Pierre Pureur, and Eoin Woods have taken their extensive enterprise architecture experience and applied it to the practical aspects of continuous architecture in real-world environments. Continuous Architecture in Practice provides hands-on advice for leveraging continuous architecture in real-world environments and illuminates architecture's changing role in the age of Agile, DevSecOps, and cloud platforms. This guide will help technologists update their architecture practice for new application challenges. As part of the Vaughn Vernon Addison-Wesley Signature Series, this title was hand-selected for the practical, delivery-oriented knowledge that architects and software engineers can quickly apply. It includes in-depth guidance for addressing today's key quality attributes, including cross-cutting concerns such as security, performance, scalability, resilience, data, and innovation. Each key technique is demonstrated through a start-to-finish case study reflecting the authors' deep experience evolving complex software environments. Create sustainable, coherent systems that meet functional requirements and the quality attributes stakeholders care about Understand team-based software architecture and architecture as a "flow of decisions" Reflect varied data technologies and crucial issues of data management, integration, and change Architect for security, including continuous threat modeling and mitigation Use architecture to improve performance in continuous delivery environments Architect for scalability and scale microservices and serverless environments Use architecture to apply emerging technologies more successfully.
Online resource; Title from title page (viewed June 7, 2021)